Implementasi Jaminan Reklamasi pada Perusahaan Pertambangan Batubara - Muhammad Yunus; Bagya Agung Prabowo (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
According to Law Number 3 of 2020 as an amendment to Law Number 4 of 2009 concerning Mineral and Coal Mining and Government Regulation Number 78 of 2010 concerning Reclamation and Post-mining, it requires companies to carry out post-mining reclamation. There are 1,735 ex-mine pits that are not reclaimed in East Kalimantan, which is evidence of the poor responsibility of coal mining managers. As a result, ex-mines that are left gaping without reclamation and recovery will cause 40 people to die by 2021. The purpose of this research is to find out the responsibilities of mining managers and how the community's legal protection of guarantees for reclamation of coal mining companies in East Kalimantan. This research is a non-doctrinal legal research with a socio-legal approach. Researchers focus on the social, economic, political and cultural contexts that develop and influence law. The results of this study indicate that coal mining managers in East Kalimantan are not fulfilling their responsibilities as they should. Environmental interests are often ignored and defeated by economic and political interests, various regulations regarding the environment and post-mining reclamation are unable to compel related parties to carry out statutory orders. Furthermore, regarding the legal protection of the community, it is also not implemented properly, as evidenced by the dozens of souls who died needlessly, which did not even receive serious attention from the regional government of East Kalimantan Province. From each incident the death of the victim in the mining pit was never completely resolved through legal channels, only 1 (one) case was convicted and the sentence imposed was very light, namely only 2 (two) months, while the rest of the cases had no follow-up.